Strategi Pembelajaran dalam Meningkatkan Kemampuan Menulis Teks Narasi pada Pembelajaran Bahasa Indonesia - Rika Berliana Dabukke; Siti Enik Mukhoiyaroh Bambang (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Writing is an important language skill to develop in Indonesian language learning, particularly in writing narrative texts. However, many students still experience difficulties in finding ideas, developing storylines, choosing appropriate vocabulary, and constructing sentences effectively. Therefore, appropriate learning strategies are needed to improve narrative writing skills. This study aims to identify, analyze, and describe various effective learning strategies in improving narrative writing skills in Indonesian language learning. The study used a qualitative method with a literature review approach. Research data were obtained from scientific articles accessed through Google Scholar with the help of the or Perish application. The articles analyzed were published in the period 2020–2026 and selected based on their relevance to the research topic. Data collection techniques were carried out through documentation studies and literature studies, while data analysis used content analysis. The research results indicate that various learning strategies are effective in improving narrative writing skills, including brainstorming techniques, expository strategies, Direct Writing Activities, the Contextual Teaching and Learning (CTL) approach, fun learning, Project-Based Learning (PjBL), digital literacy, the use of animated video media, local wisdom-based learning, and the Genre-Based approach. These strategies have been proven to improve students’ ability to develop ideas, structure storylines, enhance creativity, learning motivation, and improve the quality of narrative writing. The implications of this research indicate that selecting varied, innovative learning strategies that are appropriate to student characteristics can optimally support the development of narrative writing skills in Indonesian language learning.